Larousse Gastronomiques : the world's greatest culinary encyclopedia. (New York : Clarkson Potter Publishers, 2009)
"Has now been updated to add the latest advancements that have forever changed the way we cook, including modern technological methods, such as sous-vide cooking and molecular gastronomy. All-new color ingredient-identification photographs give this edition a fresh, elegant look. And...Larousse features more than 400 reportage photos--candid images of upscale restaurants from around the world--that give behind-the-scenes access into the kitchens where the finest food is created" -- From the publisher
Includes index.
Keywords: FOOD -- ENCYCLOPEDIAS